Numerical assessment of the seismic vulnerability of the historical earthen remains of the Mansourah enclosure (Tlemcen, Algeria): influence of geometry and identification of critical damage zones (Fracture and Structural Integrity, 2026)
This work primarily aims to carry out a numerical assessment of the seismic vulnerability of the historical Rammed Earth (RE) remains of the enclosure of Mansourah, a small town in the Wilaya (Province) of Tlemcen, in northwestern Algeria. For the purpose of successfully conducting this work, it was deemed appropriate to consider six geometric configurations, which were analyzed using three-dimensional finite element models developed in ANSYS with elastoplastic behavior based on the Drucker-Prager criterion. Two seismic excitations were applied successively along the two orthogonal horizontal directions X and Y. In addition, the analysis essentially focused on five major physical indicators, i.e. the principal tensile and compressive stresses, equivalent stress, equivalent plastic deformation, and maximum displacement. The results showed a spatial coherence of the critical zones that are most exposed to damage, for all the cases studied. These zones are located mainly at the base of the intermediate walls, at the ends of the free walls, and in the thickness transition zones of the walls constituting the towers. The vulnerability classification, from the most critical to the most stable case, was found to be as follows: Structure 05, 04, 01, 03, 02, 06. These findings facilitate the orientation and prioritization of strategies for the reinforcement and preservation of historic monuments built with RE.
Keywords: Rammed-earth; Nonlinear behavior; critical zones; damage; Seismic vulnerability; equivalent plastic deformation; Drucker–Prager criterion